EXPLORATION OF FACTORS OF FORMATION OF FOOD HABITS AND MODERN TENDENCIES OF SCHOOL FOOD AT CHILDREN OF DIFFERENT AGE - Clubei, Svetlana; Pogorelova, Kateryna; Saltykova, Halyna; Gnyloskurenko, Ganna; Korol, Elena (The Ukrainian Scientific Medical Youth Journal, 2021)
All over the world, the number of people suffering from diseases of the gastrointestinal tract is increasing every year. Digestive diseases are also not the last place in the struc- ture of causes of death. One of the main causes of gastrointestinal pathology is irrational, unhealthy diet, the foundations of which are often laid in childhood. Education at school is a change in diet, the child›s independence in choosing food. At school age, certain food choices are gradually fixed in the eating habit and determine the formation of the health of children and adults. The aim of the study was to investigate the factors that play a leading role in the formation of eating habits in schoolchildren of different ages, and the attitude of schoolchildren to nutrition in sec- ondary schools in Kyiv. At the research took part 267 students of secondary schools in Kyiv, 214 of them - are younger students (8-11 years), and 53 - older students (12-17 years). Two questionnaires presented to students in grades 3-4 and grades 5-11, certain questions allowed us to assess the impact on food choices of factors such as family eating habits, friends› opinions, advertising, and personal beliefs. Also, the answers to certain questions were grouped in such a way as to assess the trends in school nutrition and the readiness of the student›s family to follow the rules of healthy eating with the child. The criterion for exclusion from the study was the presence of diseases that require any dietary restrictions. The results of the study: according to the survey, 42-47% of young children have the greatest influence on the forma- tion of eating habits of family eating habits and their own beliefs, while for most older children (75.5%) the influence of family eating habits pre- vails. Among 267 students who are in school for an average of about 6-8 hours, have a full meal 178 (66%), almost a third use the service «ready school lunches», 32% bring food from home, 1/3 of children in schools consume only fruit and water. Of the 208 students who ate lunch at school at least once, 63% of children thought it was delicious, but 37.4% said that lunch was cold and did not allow them to eat it with pleasure. Only 13% of children noted that lunches were not tasty. The majority of young children (82%) believe that their parents will support them in choosing healthy food, compared to 47.1% of high school students. These results can be used by teachers to understand the main points of influence on the formation of healthy eating skills in children, and questionnaires can be used to assess school nutrition and to assess the dominant factors in the formation of eating habits in an individual child.